Misi Utama Tokoh Monster dalam Novel Frankenstein in Baghdad Analisis Semiotika Roland Barthes - Karay Lazuardi Novanka; Zubair Zubair (STIQ Amuntai, 2026)
This study aims to examine the semiotic construction and deconstruction of the Monster's main mission in Ahmed Saadawi's novel Frankenstein in Baghdad. Amid the legal vacuum in post-2003 Iraq, the Monster emerges as a justice-seeker, presenting a complex teleological paradox. This research employs a descriptive-analytical qualitative method. Robert Stanton's Structuralism is used to map the character's narrative function, while Roland Barthes' Semiotics is applied to dissect the meaning-making process at the denotative, connotative, and mythical levels. The findings reveal that the Monster's mission undergoes a radical semantic distortion. Initially, it is constructed into a